Kabale University Interdisciplinary Research Journal (KURJ) - Siraje, Kaaya; George Stanley, Kinyata (Kabale University Interdisciplinary Research Journal, 2022)
Kabale University Interdisciplinary Research Journal (KURJ) is a multidisciplinary journal accepting high quality original research articles, letters and commentaries on a wide range of disciplines. KURJ intends to bridge the gap between research and innovation within the University environment and to bring to fore a multidisciplinary university based journal that can be used for disseminating high quality and impactful publications